Extreme laser pulses for non-thermal fusion ignition of hydrogen–boron for clean and low-cost energy. (21st September 2018) - Hora, Heinrich; Eliezer, Shalom; Miley, George H.; Wang, JiaXiang; Xu, YanXia; Nissim, Noaz
Abstract: After achieving significant research results on laser-driven boron fusion, the essential facts are presented how the classical very low-energy gains of the initially known thermal ignition conditions for fusion of hydrogen (H) with the boron isotope 11 (HB11 fusion) were bridged by nine orders of magnitudes in agreement with experiments. This is possible under extreme non-thermal equilibrium conditions for ignition by >10 PW-ps laser pulses of extreme power and nonlinear conditions. This low-temperature clean and low-cost fusion energy generation is in crucial contrast to local thermal equilibrium conditions with the advantage to avoid the difficulties of the usual problems with extremely high temperatures.